Body mass index associated to rs2021966 ENPP1 polymorphism increases the risk for gestational diabetes mellitus. (January 2015) - Tarquini, Federica; Picchiassi, Elena; Centra, Michela; Pennacchi, Luana; Bini, Vittorio; Cappuccini, Benito; Torlone, Elisabetta; Coata, Giuliana; Di Renzo, Giancarlo; Brancorsini, Stefano
Abstract Gestational diabetes mellitus (GDM) is a condition of impaired glucose tolerance occurring in 1–14% of all pregnancies. This wide range reflects pathological involvement of single nucleotide polymorphisms (SNPs) and maternal weight as risk factors. This study evaluated the association of genetic component and maternal factors to identify women with higher risk of developing GDM. About 240 pregnant women characterized by negative Oral Glucose Tolerance Test (−OGTT) and 38 with positive OGGT (+OGTT) were enrolled. SNPs for ENPP1, NRF1, VEGFA, CEBPA, and PIK3R1 were analyzed by SNP genotyping. An association study was performed and differences in genotype and allele frequencies between cases and controls were analyzed by χ2 test. +OGTT was associated to high values of pre-gestational body mass index (BMI) and age. SNP for ENPP1 gene was associated to +OGTT, while genetic variants for other genes did not correlate to GDM. ENPP1 homozygous for A allele and heterozygous showed altered frequencies in +OGTT when compared with −OGTT. Association of both pre-gestational BMI and age with AA homozygous genotype increased significantly the risk to +OGTT. Our results demonstrate that correlation of age and pre-gestational BMI with homozygous for A allele increased significantly the risk of impaired glucose tolerance and GDM.